Machining of additively manufactured parts: implications for surface integrity - Oyelola, Olusola; Crawforth, Pete; M'Saoubi, Rachid; Clare, Adam T. (Elsevier, 2016)
Additive manufacturing methods continue to move towards production ready technologies with the widely extolled virtues of rapid transition from design to part and enhanced design freedoms. However, due to fundamental limitations of laser based processes for metal additive manufacturing, there is a significant ongoing need for these parts to be subject to additional machining operations. This paper reports on a study to investigate the machining behavior and surface integrity of Ti-6Al-4 V components which have been produced by direct metal deposition using wire feedstocks. Simple geometries are produced and the resulting effect of tooling type is reported. Inhomogeneities in the deposition process as a result of non-uniform cooling and porosity are shown to have a deleterious effect on the surface integrity of the resulting part and the machinability of such components. In addition, strategies for the machining of AM parts which consist of graduated material structures are also proposed here.